Effective big data management and opportunities for implementation - Singh, Manoj Kumar 1972-; Kumar G., Dileep 1982- (A volume in the Advances in data mioning and database management (ADMDM) book series, 2016)
This book explores emerging research on the ever-growing field of big data and facilitates further knowledge development on methods for handling and interpreting large data sets, providing multi-disciplinary perspectives fueled by international research.